Panel data evidence on productivity spillovers from foreign direct investment: Firm-level measures of backward and forward linkages - Pavel Vacek (Charles University in Prague, Institute of Economic Studies (IES), 2010)
I examine whether foreign direct investment increases the productivity of manufacturing firms. I test the proposition that local firms benefit from supplying multinational firms (spillovers through backward linkages) and by purchasing inputs from multinationals (spillovers through forward linkages). The existing literature on productivity spillovers has relied on industry-level proxies for spillovers. I identify spillovers directly at the firm level. I have conducted field work in the Czech manufacturing sector and built a unique data set that enabled me to construct firm-level measures of backward and forward linkages. My results provide strong support for the existence of productivity spillovers through backward linkages.
Keywords: F23; 330; FDI; spillovers; forward-backward linkages; Direktinvestition; Produktivität; Spillover-Effekt; Multinationales Unternehmen; Verarbeitendes Gewerbe; Tschechische Republik